Minority Students’ Perspectives on Study Abroad: A Case from One Historically Black College and University (Comparative & International Education Series, 2021)
Study abroad programs are growing in institutions across America and around the world as more and more institutions focus on the need for internationalization across programs. Student participation in study abroad programs is also increasing, with one exception.  Minority student participation has not kept pace with other groups. Is this lack of participation due to economic issues, fear, and language barriers or are there potentially other factors that might be affecting minority student participation rates? This chapter investigates minority students’ perspectives on study abroad programs from within the Historically Black Colleges and Universities as study abroad programs are important to the overall educational experience of the entire community.